Feasibility and preliminary experience of single-incision plus one-port laparoscopic total gastrectomy with Overlap esophagojejunostomy for gastric cancer: A study of 10 cases - Yin, Jiu-Heng; Chen, Yi-Hui; Ren, Yan-Bei; Wang, Rong; Su, Shuai; Jiang, En-Lai; Li, Yun-Bo; Wang, Ting; Xiao, Wei-Dong; Du, Guang-Sheng (Frontiers in Surgery, 2023)
Abstract Background: This study aimed to explore the feasibility and safety of single-incision plus one-port laparoscopic total gastrectomy (SITG+1) with Overlap esophagojejunostomy (SITG+1-Overlap) and to share preliminary experiences. Methods: This retrospective study included 10 patients with gastric cancer located in the cardia or body who underwent SITG+1-Overlap between August 2020 and October 2021.The demographics, tumor characteristics, postoperative outcomes, and short-term complications of all the enrolled patients were summarized and statistically analyzed. Data were expressed as mean± standard deviation (SD) if they were normally distributed. Otherwise, Median (Quartile1, Quartile3) was used. Results: In the collective perioperative data of these 10 patients who underwent radical gastrectomy, the median of the length of transumbilical incision and blood loss were 3.0 cm and 100.0 ml respectively, and the mean operation time and 385.5 ± 51.6 minutes. Postoperative data indicated that the gastric tube was removed on 2.0 (2.0, 3.0) days, and the timing of first feeding, activity, flatus, and defecation was 1.5 (1.0, 2.0) days, 2.0 (2.0, 2.0) days, 3.0 (2.0, 3.0) days, and 3.8 ± 0.6 days, respectively. The timing of drainage tube removal was 4.6 ± 1.0 days after operation. The duration of hospital stay was 7.5 ± 1.2 days and the VAS pain scores for the 3 days following surgery were 3.0 (2.0, 3.3), 2.0 (2.0, 3.0), and 1.5 (1.0, 2.0) respectively. The mean number of retrieved lymph nodes was 30.7 ± 13.2. Most biochemical indicators gradually normalized with the recovery of the patients after surgery. No 30-day postoperative complications were noted. Conclusions: For the first time, our preliminary data indicate the feasibility and safety of Overlap esophagojejunostomy in SITG+1 surgery. This modified Overlap procedure has the potential to simplify the reconstruction procedure and lower the technical challenge of SITG+1 radical gastrectomy for cardia or upper gastric cancer in the early and advanced stages.